Рignoris Capio During Roman History: Рignoris Capio According to the Institutes of Gaius - Milutin, Milan M (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
Abstract: Рignoris capio used to exist since the earliest times of Roman history until its end. In terms of its primordial form, which consisted of creditor’s act of taking debtor’s thing in pledge until the repayment of the debt and pronouncing certain solemn words, the most significant source are the Institutes of Gaius. Gaius classified pignoris capio into legisactios. However, this classification raised controversies which we addressed, reaching nevertheless the answer which supports Gaius’s claim. Gaius tells us that pignoris capio was sometimes used based on customs, while sometimes based on the laws. In terms the application of pignoris capio based on customs, we attempted to answer the question of whether pignoris capio came into being even before the introduction of legisactios. In relation to aes militare, the answer is negative, because the application of pignoris capio for its securitization did not start before 406 BC, it lasted while salaries for soldiers were paid by tribunus aerarius, against whom pignoris capio could only have been used, and it ceased to exist when this duty was taken upon by quaestor. Contrary to that, in reference to aes horidiarium, the answer is probably positive, and pignoris capio for its securituzation was used against widows and ceased to exist with the extinction of aes hordiarium (probably in 342 BC). In relation to aes equestre, if pignoris capio for its securutization even existed, the answer is positive as well. However, this right disappeared when, instead of a horse, money from the state treasury was given for the purposes of supplying a night with a horse. While all the soldiers had the right to aes militare, the right to aes equestre and aes hordiarium was the priviledge of equites equo publico. In terms of the application of pignoris capio based on the law, we also analyzed time references of its duration, type(s) of laws with which it could have been regulated, rights of creditors and debtors related to the pledged thing and conditions under which it could have existed.